Effect of Temperature and N-Doping on the Distribution of Bamboo Waste Pyrolysis Products Using Quartz Tube Furnace - Mufandi, Ilham; Kholis, Muhammad Nur; Hamawi, Mahmudah; Ardani, Much Taufik; Kusuma, Hafidha Ayu (Eksergi, 2025)
This study investigates the effect of temperature and nitrogen doping (N-Doping) on the pyrolysis of bamboo waste to optimize the distribution of biochar, bio-oil, and gas products. Bamboo waste as raw material was applied to pyrolysis in a quartz tube furnace reactor at temperatures of 300°C, 400°C, 500°C, and 600°C under two atmospheric conditions: pyrolysis with nitrogen (PN) and pyrolysis without nitrogen (PWN). Results reveal that temperature significantly influences product distribution, with bio-oil yield peaking at 500°C (52% in PN) and decreasing at higher temperatures due to secondary cracking. Nitrogen doping enhances bio-oil production by preventing oxidation and reducing secondary reactions, leading to a bio-oil yield increase from 16.52% in PWN to 55.32% in PN at 500°C. Conversely, PWN conditions resulted in higher biochar yield due to partial oxidation. Gas yield increased at elevated temperatures in both conditions, attributed to thermal cracking and reformation processes. These findings emphasize the importance of controlled temperature and atmospheric conditions in maximizing the efficiency and product quality of bamboo waste pyrolysis. The results provide valuable insights into sustainable biomass conversion strategies, contributing to renewable energy development and bamboo waste valorization.